Web based professional development tool for lecturers / Jayabalan Sathiasulan - Jayabalan, Sathiasulan (2005)
Malaysia is now moving heavily towards the era of Information Technology (IT) and the Internet technology is really an industry that is growing larger day by day. However, not many people appreciate these technologies and use them to simplify their work in life. We, who are a student and a citizen of the IT society should know and use these technologies to help us in real life situations. web based professional development tool for lecturers is a system that will help lecturers of Faculty of Computer Science and Information Technology (FCSIT), to build a personal websites without any programming knowledge barrier. Currently, many lecturers having their websites with limited function and unprofessional layout. The main objective of this system is to facilitate lecturers to build a website without using any web developing software and without any web programming knowledge. The system is developed to support four types of process, the layout manages process, data input process, download process and upload process. Each process has few functions with user friendly environment to make ease the web development process. Moreover some optional also given to lecturers to develop their website with advanced web function such as forum and search with just a single dick. Therefore, I believe that this system will benefit all lecturers from FSCIT when it's implemented later.